RESPON STABILITAS SISTEM YANG MENGGUNAKAN GOVERNOR KONVENSIONAL DAN GOVERNOR FUZZY LOGIC - Arifin, Yusnaini (MEKTEK, 2011)
This paper aims to know how the conventional and fuzzy logic governor respons by load/disturbance changeand how the plant can achieve steady state condition after the load/disturbance change. This research usedsimulation methode which analyze respons of plant using conventional and fuzzy logic governor. In thissimulation, load changed 0,05 pu and 0,5 pu respectively.This study showed that by increasing of loads, 0,05 pu and 0,5 pu, system using conventional governor willachieve steady state condition at the instant of 30 and 35th second and have frequency deviation -0,0024 puand -0,024 pu respectively. Whereas system using fuzzy logic governor will achieve steady at the time of 27thand 33rd second, with frequency deviation are -0,0004 pu and -0,0055 pu. Generally, system using fuzzylogic governor has better performance than system using conventional governor